Evaluation of Serum Leptin Level with Genes (LEPR and TMEM18) Expiration in Obese Individuals - Khalaf, Marwa M.; Maleek, Muthana I. (American Journal of Biology and Natural Sciences, 2025)
Background: obesity is linked to early death and poses a severe danger to public health. Non-communicable diseases, including type 2 diabetes, cardiovascular conditions, high blood pressure, and various cancers, significantly contribute to the global health burden. Studying the genes, hormones, and proteins that has correlation with obesity will help explain why some people, even in identical situations, are more likely to become obese than others. Aim: Identify the effect of Leptin hormone, gene expiration of LEPR and TMEM18 and differences between obese and healthy individuals in obesity people. Method: This study was carried out in laboratories of College of Science, Wasit University in Iraq form November 2023 to July 2024.This study were include 80 peoples the ages (18-50) they were measuring the BMI of them . Fifty obese people (25 male and 25 female) they are diagnosed clinically. The control group consists of 20 apparently healthy individuals (10 male and 10 female). The current study was in agreement with hospital ethics and approvals from all participants. Measuring Leptin, LEPR and TMEM18 Genes expiration in obese and control groups by EIESA assay and Real Time PCR according to type of test. Results. The Results was showed that mean concentrations of leptin hormone and LEPR were significantly lower in obese individuals than in the control group. Leptin hormone 1.47 ± 0.061 (obese) vs. 2.35 ± 0.411 (control) (P = 0.002). LEPR 0.52 ± 0.18 and 1(control) (P= 0.001).Also, the mean levels TMEM18 genes were significantly higher in obese individuals compared control group. TMEM18 3.43 ± 0.78 (obese) vs. 1.00 (control) (P = 0.001). Conclusions: It is concluded from the present study that the gene expression of LEPR, TMEM18 and Leptin hormone important roles in the development and severity of obesity.